Hasil Kadar HbA1C Penderita Diabetes Melitus Tipe 2 Pada Kelompok Prolanis Di Puskesmas Juhar Tahun 2023 - Helny Zuraini Tarigan; Riduan Benny (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. The International Diabetes Federation (IDF) estimates that the number of diabetes sufferers in Indonesia could reach 28.57 million in 2045. This number is 47% greater than the number of 19.47 million in 2021. This research was conducted on patients who had been diagnosed with type 2 DM who were members of the Prolanis group. Prolanis is a health service system that aims to improve the quality of life of participants with chronic diseases, one of which is Diabetes Mellitus type 2. HbA1c is a substance formed from the reaction between glucose and hemoglobin. HbA1c is one of the parameters for assessing glycemic control (patient compliance). The research entitled Analysis of HbA1c Levels in Type 2 Diabetes Mellitus Sufferers in the Prolanis Group at the Juhar Community Health Center aims to analyze and measure HbA1c levels in Type 2 Diabetes Sufferers. The research method used was Descriptive Cross-sectional. The examination material used is median cubital vein blood with EDTA anticoagulant. From the results of the examination, 25 samples were obtained, of which 12 patients had HbA1c levels >8% with criteria for poor DM control, 6 patients had HbA1c levels of 6.5-8% with criteria for moderate DM control, and there were 7 patients with HbA1c levels <6.5%. with the criteria for good DM control. From the results of this study, it was found that controlling DM at the Juhar Community Health Center there were 14 patients who had HbA1c values above 6.5 and after follow-up for the next 6 months, some had HbA1c levels that decreased and others that increased. To obtain good DM control, it is best for people with diabetes to have an HbA1c check every 3 months as part of diabetes management and this management is very important to carry out in health services, including primary level health services.